Answer:
![y = (-1)/(2)(x-3)](https://img.qammunity.org/2021/formulas/mathematics/college/5xtoz5x3xhfzy8q1cvlu9gdewm2eiv505t.png)
Explanation:
To determine the inverse of an equation, simply switch the places of the 'x' and 'y' variables. Therefore:
f(x) = -2x + 3
Use 'y' in place of f(x).
y = -2x + 3
Switch the 'x' and the 'y':
x = -2y + 3
Subtract '3' from both sides:
x - 3 = -2y
Divide both sides by '-2':
![y= (x-3)/(-2)](https://img.qammunity.org/2021/formulas/mathematics/college/cdi8iijhpsnuijiwxyn7zc35qaukc9bkfc.png)
Simplify:
![y = (-1)/(2)(x-3)](https://img.qammunity.org/2021/formulas/mathematics/college/5xtoz5x3xhfzy8q1cvlu9gdewm2eiv505t.png)